2012
DOI: 10.1177/1460408612458878
|View full text |Cite
|
Sign up to set email alerts
|

Rectal trauma in adults

Abstract: Rectal trauma is associated with high rates of morbidity and mortality and generally affects young males due to its aetiology of violent crime and vehicular collision. Historically, management has followed principles derived from military practice, with faecal diversion, pre-sacral drainage and distal washout being mandatory. Civilian trauma studies examining management of colon and rectum injuries from the early 1950s identified major differences in the level of energy transfer between civilian and military w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 86 publications
(125 reference statements)
0
10
0
1
Order By: Relevance
“…Barsakların distalindeki patolojik olayın veya anostomozun iyileşmesi sürecinde, perinenin travmatik defektleri gibi durumlarda, bölgenin dışkı akımından uzak tutulması amacıyla kolostomi açılabilmektedir (3). Geçici ve kalıcı olmak üzere iki tip kolostomi söz konusu olup, anorektal bölge travma / hastalıklarında kolostomi açma gereği duyulduğunda genellikle geçici kolostomi açıl-maktadır (4,5). Ancak anorektal bölgenin yüksek enerjili çoğul travmaları sonucu gelişen ve anorektumun çı-karılmasına neden olan durumlarda kalıcı kolostomiler açılabilmektedir (6).…”
Section: Discussionunclassified
“…Barsakların distalindeki patolojik olayın veya anostomozun iyileşmesi sürecinde, perinenin travmatik defektleri gibi durumlarda, bölgenin dışkı akımından uzak tutulması amacıyla kolostomi açılabilmektedir (3). Geçici ve kalıcı olmak üzere iki tip kolostomi söz konusu olup, anorektal bölge travma / hastalıklarında kolostomi açma gereği duyulduğunda genellikle geçici kolostomi açıl-maktadır (4,5). Ancak anorektal bölgenin yüksek enerjili çoğul travmaları sonucu gelişen ve anorektumun çı-karılmasına neden olan durumlarda kalıcı kolostomiler açılabilmektedir (6).…”
Section: Discussionunclassified
“…The study demonstrated a significant correlation between pelvic fractures, massive soft tissue injury and rectal injuries, resulting in a mortality rate of 33%. High-energy transfer injuries usually result in rectal injuries that require some form of local surgical debridement and repair in combination with a diverting colostomy for faecal diversion 7 8 11. In a cohort of colorectal injuries in 977 coalition forces serving in Iraq and Afghanistan rectal injury led to faecal diversion twice as often as colonic injury, with more than half of patients requiring an ‘ostomy’ (56.2%) 12…”
Section: Discussionmentioning
confidence: 99%
“…The decision-making strategy for the initial treatment of rectal injuries relies on a number of factors that include the anatomic site and cause of rectal injury, physiologic condition of the patient, and antibiotic use [2,3]. It has been recognized that the rectal injuries above the peritoneal reflection are readily accessible and amenable to treatment as for colonic injuries, and hence they are classically treated with primary repair with or without proximal diversion [4]; on the other hand, the extraperitoneal rectal injuries are usually more difficult to access and direct repair is usually impossible [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent multi-institutional study [8] found that the presacral drainage and rectal washout were independently associated with a three-fold increase in abdominal complications, recommending to avoid these measures in the management of extraperitoneal rectal injuries. While the role of presacral drainage and distal rectal washout in the setting of civilian rectal injury is debatable, they still have a place in the battlefield or other high-energy transfer rectal injuries in order to decrease septic complications, as Barkley et al [5] implied.…”
Section: Introductionmentioning
confidence: 99%